2019
DOI: 10.1186/s12974-019-1513-5
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting diode therapy protects against ventricular arrhythmias by neuro-immune modulation in myocardial ischemia and reperfusion rat model

Abstract: Background Sympathetic overactivation and inflammation are two major mediators to post-myocardial ischemia-reperfusion (I/R)-induced ventricular arrhythmia (VA). The vicious cycle between microglia and sympathetic activation plays an important role in sympathetic hyperactivity related to cardiovascular diseases. Recently, studies have shown that microglial activation might be attenuated by light-emitting diode (LED) therapy. Therefore, we hypothesized that LED therapy might protect against myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Caspase‐1 NLRP3 and ASC are components of NLRP3 inflammasomes that can cause cardiac inflammation and cardiac dysfunction via IL‐1β and TGF‐β1 release 13–16 . Inhibiting TGF‐β and IL‐1β expression can alleviate cardiac dysfunction in ischemic VA‐HF 9–11 . The present study found that NLRP3 inflammasomes and the expression of IL‐1β and TGF‐β1 gradually increased in healthy rats, and in rats with HF and VA‐HF.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Caspase‐1 NLRP3 and ASC are components of NLRP3 inflammasomes that can cause cardiac inflammation and cardiac dysfunction via IL‐1β and TGF‐β1 release 13–16 . Inhibiting TGF‐β and IL‐1β expression can alleviate cardiac dysfunction in ischemic VA‐HF 9–11 . The present study found that NLRP3 inflammasomes and the expression of IL‐1β and TGF‐β1 gradually increased in healthy rats, and in rats with HF and VA‐HF.…”
Section: Discussionsupporting
confidence: 50%
“…IL‐1β aggravates VA induced by ischemia 8 . Inhibiting the expression of TGF‐β, IL‐1β, IL‐6, IL‐18, and TNF‐α can reduce VA in ischemic HF, which plays a role in anti‐VA 9–11 . Nucleotide‐binding oligomerization domain‐like receptor family pyrin domain containing 3 (NLRP3) inflammasomes were recently discovered as inflammatory response regulators that consist of NLRP3, ASC, and caspase‐1.…”
Section: Introductionmentioning
confidence: 99%
“…LED therapy might reduce myocardial ischemia/reperfusion-induced ventricular arrhythmias by attenuating microglial and sympathetic over-activation. They also proved that LED therapy has the same indirect effects of sympathetic activity in a rat model of acute myocardial ischemia/reperfusion injury (Wang et al, 2019c). This indicates that LED affects the ANS through the inhibition of inflammation rather than through direct effects.…”
Section: Light-emitting Diode Therapy In the Modulation Of The Cans Fmentioning
confidence: 87%
“…Also, there is an association between obesity and inflammation [12]. A recent study showed that light-emitting diode (LED) therapy protected against myocardial IRI-induced ventricular arrhythmia by suppressing microglial activation and the expression of inflammatory cytokines in the ischemic myocardium [26]. Salahshoor et al showed that royal jelly had antioxidant and anti-inflammatory properties that reduced IRI-induced renal injury [27].…”
Section: Discussionmentioning
confidence: 99%